Silicon composite material and application thereof
By using a silicon composite material containing liquid metal gallium and indium in the negative electrode sheet of the lithium-ion battery, the problem of SEI film rupture caused by volume changes in the silicon material during the deintercalation process is solved, and the structural stability and cycling performance of the battery are achieved. Improvement.
Patent Information
- Application Number
- CN202411573010.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The silicon material in lithium-ion batteries is prone to undergo huge volume changes during the deintercalation process of lithium, resulting in repeated rupture and reconstruction of the SEI film, affecting the structural stability of the negative electrode sheet and the cycling performance of the battery.
A silicon composite material is used that contains the sum of the mass percentage of the liquid metal gallium and indium, gallium and indium, and the intermediate layer comprises liquid metal by forming an intermediate layer and an outer layer on the silicon core. Gallium and indium, the outer layer includes metal organic hybrid glass, to stabilize the silicon material.
This silicon composite material is not prone to expansion in battery applications, and can form a stable SEI film, improving the first-effect and cycling performance of the battery.
Smart Images

Figure CN119400835A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a silicon composite material and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have become the main electrochemical energy storage system since their commercialization. In order to improve the energy density of LIBs, silicon (Si) is considered to be one of the promising candidate materials to replace commercial graphite because of its high theoretical capacity.
[0003] However, during the process of lithium insertion and extraction in the battery, silicon is prone to huge volume changes, which will cause the SEI film to rupture and rebuild repeatedly, which is not conducive to the structural stability of the negative electrode sheet and, in turn, the cycle performance of the battery. Summary of the invention
[0004] The present invention provides a silicon composite material. When a negative electrode sheet comprising the silicon composite material is applied to a battery, the silicon composite material is not easy to expand, can form a stable SEI film, and can improve the cycle performance of the battery.
[0005] The present invention provides a silicon composite material, which comprises liquid metal gallium and indium. In the silicon composite material, the sum of the mass percentages of gallium and indium is 0.05-0.2%.
[0006] The silicon composite material as described above, wherein, based on the total mass of gallium and indium, the mass percentage of gallium is 68-74%, and the mass percentage of indium is 26-32%.
[0007] The silicon composite material as described above, wherein it comprises a silicon core, an intermediate layer and an outer layer;
[0008] The middle layer is located on at least a portion of the surface of the silicon core, and the outer layer is located on at least a portion of the surface of the middle layer;
[0009] The middle layer includes liquid metal gallium and indium, the outer layer includes metal-organic hybrid glass, and the silicon core is micron-sized silicon material.
[0010] The silicon composite material as described above, wherein the Dv50 of the silicon core is 5-30 μm;
[0011] Preferably, the Dv50 of the silicon core is 20-30 μm.
[0012] The silicon composite material as described above, wherein the specific surface area of the silicon composite material is 200-2000m 2 / g; and / or,
[0013] The pore size of the silicon composite material is 1.3-2.7 nm; and / or,
[0014] The Dv50 of the silicon composite material is 10-50 μm; and / or,
[0015] The aspect ratio of the silicon composite material is 1-5; and / or,
[0016] The silicon composite material CO 2 The adsorption enthalpy is 10-40 kJ / mol.
[0017] The silicon composite material as described above, wherein the specific surface area of the silicon composite material is 800-2000m 2 / g; and / or,
[0018] The Dv50 of the silicon composite material is 35-50 μm; and / or,
[0019] The aspect ratio of the silicon composite material is 1-2; and / or,
[0020] The silicon composite material CO 2 The adsorption enthalpy is 15-30 kJ / mol.
[0021] The silicon composite material as described above, wherein the mass ratio of the silicon core, the metal organic hybrid glass and the liquid metal in the silicon composite material is (50-100): (5-20): 1;
[0022] Preferably, in the silicon composite material, the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal is (70-90):(8-12):1.
[0023] The silicon composite material as described above, wherein the metal organic hybrid glass comprises metal ions and ligands, the metal ions include at least one of copper ions, zinc ions, cobalt ions, iron ions, ferrous ions, zirconium ions, aluminum ions and chromium ions, and the ligands include at least one of 1,3,5-benzenetricarboxylic acid, 2'-amino-[1,1':4',1"-terphenyl]-4,4"-dicarboxylic acid, terephthalic acid, dimethylimidazole, 2,5-dimethylterephthalic acid, 2,5-diaminoterephthalic acid and 2-amino-4,4'-biphenyldicarboxylic acid;
[0024] And / or, the micron-sized silicon material is at least one of micron-sized silicon carbide, micron-sized elemental silicon, micron-sized silicon oxide, micron-sized silicon nitrogen composite and micron-sized silicon alloy.
[0025] The present invention provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes the silicon composite material described above.
[0026] The negative electrode sheet as described above, wherein the mass percentage of the silicon composite material in the negative electrode active layer is 2-50%;
[0027] And / or, the sum of the mass percentages of gallium and indium is 0.01-0.04%; preferably, in the negative electrode active layer, the mass percentages of silicon, gallium and indium are (1-1.8): (0.0136-0.0148): (0.0052-0.0064).
[0028] The negative electrode sheet as described above, wherein in the color spectrum of the negative electrode sheet, the ratio of the peak height to the peak bottom width is greater than 40:1.
[0029] The present invention provides a battery, comprising the negative electrode sheet as described above.
[0030] The battery as described above, wherein it further comprises an electrolyte, wherein the electrolyte comprises lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate in the electrolyte is c, mol / L; and in the negative electrode sheet, the mass percentage w of the silicon composite material satisfies:
[0031] w:c=(10-30):1;
[0032] Preferably, w:c=(15-25):1.
[0033] The battery as described above, wherein the ohmic impedance of the battery is less than 34 mΩ, the membrane impedance is less than 13 mΩ, and the charge transfer impedance is less than 30 mΩ;
[0034] Preferably, the battery has an ohmic impedance of <33 mΩ, a membrane impedance of <12.5 mΩ, and a charge transfer impedance of <20 mΩ.
[0035] The silicon composite material of the present invention comprises liquid metal gallium and indium, and the sum of the mass percentages of gallium and indium in the silicon composite material is 0.05-0.2%. When the negative electrode sheet comprising the silicon composite material is applied to a battery, the silicon composite material is not easy to expand, and a stable SEI film can be formed, thereby improving the first efficiency and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 This is a surface SEM image of the silicon composite material in Example 1 of the present invention;
[0038] Figure 2 This is a surface SEM image of the silicon composite material in Comparative Example 1 of the present invention;
[0039] Figure 3 This is a first spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1;
[0040] Figure 4 The second spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1;
[0041] Figure 5 The third spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1;
[0042] Figure 6 is a pore size distribution diagram of the silicon composite material in Example 1 of the present invention;
[0043] Figure 7 1 is an EIS curve diagram of the battery in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] A first aspect of the present invention provides a silicon composite material comprising liquid metal gallium and indium, wherein the sum of the mass percentages of gallium and indium in the silicon composite material is 0.05-0.2%. For example, the sum of the mass percentages of gallium and indium in the silicon composite material may be 0.05%, 0.07%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18% or 0.2%, etc.
[0046] The inventors found in their research that when the sum of the mass percentages of gallium and indium in the silicon composite material meets the above range, the negative electrode sheet including the silicon composite material can not only improve the energy density of the battery, but also form a stable SEI film when applied to the battery. The negative electrode sheet has excellent self-repairing ability and can improve the initial efficiency and cycle performance of the battery. Too little gallium and indium will cause the SEI to break, lose its repair ability, and reduce electrochemical performance; too much gallium and indium will reduce ED and even cause a short circuit.
[0047] Further, based on the total mass of gallium and indium, the mass percentage of gallium is 68-74%, and the mass percentage of indium is 26-32%. For example, the mass percentage of gallium in gallium and indium can be 68%, and the mass percentage of indium can be 32%; or, the mass percentage of gallium in gallium and indium can be 69%, and the mass percentage of indium can be 31%; or, the mass percentage of gallium in gallium and indium can be 70%, and the mass percentage of indium can be 30%; or, the mass percentage of gallium in gallium and indium can be 71%, and the mass percentage of indium can be 29%; or, the mass percentage of gallium in gallium and indium can be 72%, and the mass percentage of indium can be 28%; or, the mass percentage of gallium in gallium and indium can be 73%, and the mass percentage of indium can be 27%; or, the mass percentage of gallium in gallium and indium can be 74%, and the mass percentage of indium can be 26%, etc. When the mass percentage of gallium and the mass percentage of indium meet the above ranges, gallium and indium can be more fully matched, further improving the self-repairing ability of the negative electrode sheet and improving the cycle performance of the battery.
[0048] Exemplarily, the mass percentage of gallium and indium in the silicon composite material can be measured in the following manner: a negative electrode sample to be tested of a certain size (e.g., 15 mm×15 mm) is cut out from an arbitrary area of the negative electrode sheet, the negative electrode sample is wrapped with copper foil, and then cut by an ion beam polisher (e.g., Hitachi Arblade 5000) under freezing conditions (e.g., -80°C) to obtain a cross-section of the negative electrode sample; the negative electrode sample is subjected to gold spraying treatment, and then a scanning electron microscope (e.g., a Sigma 300 scanning electron microscope from ZEISS, Germany) is used to scan and obtain a SEM image of the cross-section of the negative electrode sheet, arbitrarily select 5 silicon composite material particles from the image, and use an energy dispersive spectrometer (EDS) to measure the mass percentage of gallium and indium in each particle, and calculate the average value.
[0049] In some embodiments of the present invention, the silicon composite material includes a silicon core, an intermediate layer and an outer layer; the intermediate layer is located on at least a portion of the surface of the silicon core, and the outer layer is located on at least a portion of the surface of the intermediate layer; the intermediate layer includes liquid metal (LM) gallium and indium, the outer layer includes metal-organic hybrid glass (MGs), and the silicon core is a micron-sized silicon material.
[0050] In the silicon composite material of the present invention, the middle layer can be located on a part of the surface of the silicon core or on the entire outer surface of the silicon core; the outer layer can be located on a part of the outer surface of the middle layer or on the entire outer surface of the middle layer. The silicon composite material of the present invention includes, from the inside to the outside, a silicon core, an middle layer and an outer layer.
[0051] The intermediate layer includes liquid metal, which refers to metal and its alloy that is liquid at room temperature or a relatively low heating temperature. For example, the liquid metal may be a liquid alloy formed by melting gallium and indium.
[0052] Metal-organic hybrid glass is a non-crystalline material, which is a glassy MOFs material. It is an amorphous metal-organic framework material formed by metal ions or metal clusters and organic ligands through coordination bonds. Glass MOFs retain the porosity and short-range order of MOFs, while exhibiting glass-like physical properties such as mechanical stability and transparency.
[0053] Micron-sized silicon material refers to silicon material with a particle size of micron-sized.
[0054] The silicon composite material of the present invention uses liquid metal as a conductive buffer material, and uses liquid metal as a bridging agent to assemble a conductive metal-organic hybrid glass through coordination chemistry to achieve the encapsulation of the silicon core. The silicon composite material has buffering and self-healing effects, and can effectively solve the problem that the silicon composite material is broken due to expansion during the charging and discharging process of the battery, thereby causing the battery's cycle performance to decrease. The silicon composite material combines strong MGs and deformable LM, so that the battery can achieve high rate capability and cycle stability at the same time; and the polar and non-polar multi-level pores of MGs can absorb carbon dioxide and hydrogen generated during the battery cycle, reduce the battery cycle thickness, and further improve the battery cycle performance.
[0055] In some embodiments of the present invention, the Dv50 of the silicon core is 5-30 μm, for example, the Dv50 of the silicon core can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc. Preferably, the Dv50 of the silicon core is 20-30 μm. When the Dv50 of the silicon core meets the above range, the silicon core can more fully cover the middle layer and the outer layer, thereby improving the cycle performance of the battery.
[0056] In some embodiments of the present invention, the specific surface area of the silicon composite material is 200-2000m 2 / g, for example, the specific surface area of the silicon composite material can be 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g or 2000m 2 / g, etc. Preferably, the specific surface area of the silicon composite material is 800-2000m2 / g.
[0057] The specific surface area of the silicon composite material is proportional to the specific surface area of the pores of the MGs. When the specific surface area of the pores of the MGs is larger, the specific surface area of the silicon composite material is also larger. When the specific surface area of the silicon composite material meets the above range, the silicon composite material has a more sufficient contact area with the electrolyte when applied to the battery, which can increase the capacity of the battery.
[0058] In some embodiments of the present invention, the pore size of the silicon composite material is 1.3-2.7 nm, for example, the pore size of the silicon composite material may be 1.3 nm, 1.5 nm, 1.7 nm, 1.9 nm, 2.1 nm, 2.3 nm, 2.5 nm or 2.7 nm, etc. When the pore size of the silicon composite material meets the above range, the formation of the SEI film in the pores of the silicon composite material can be avoided while ensuring the ionic conductivity of the silicon composite material, so that the battery has both excellent rate performance and cycle performance.
[0059] In some embodiments of the present invention, the Dv50 of the silicon composite material is 10-50 μm, for example, the Dv50 of the silicon composite material can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc. Preferably, the Dv50 of the silicon composite material is 35-50 μm. When the Dv50 of the silicon composite material meets the above range, when the silicon composite material is applied to a battery, during the charge and discharge process of the battery, the silicon composite material is not only not easy to collapse, but also has a more excellent lithium ion insertion and extraction performance.
[0060] In some embodiments of the present invention, the aspect ratio of the silicon composite material is 1-5. The aspect ratio refers to the ratio of the size of the maximum diameter in the silicon composite material to the size of the diameter perpendicular to the maximum diameter. For example, the aspect ratio of the silicon composite material can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5. Preferably, the aspect ratio of the silicon composite material is 1-2. When the aspect ratio meets the above range, the rigidity of the negative electrode SEI film can be guaranteed, the damage of the negative electrode SEI film can be avoided, and the cycle performance of the battery can be improved.
[0061] In some embodiments of the present invention, the CO of the silicon composite material2 The adsorption enthalpy is 10-40 kJ / mol, for example, CO 2 The adsorption enthalpy may be 10 kJ / mol, 15 kJ / mol, 20 kJ / mol, 25 kJ / mol, 30 kJ / mol, 35 kJ / mol or 40 kJ / mol, etc. Preferably, the CO 2 The adsorption enthalpy is 15-30 kJ / mol. 2 When the adsorption enthalpy meets the above range, during the charge and discharge process of the battery, the silicon composite material can more fully adsorb the carbon dioxide and hydrogen generated during the charge and discharge process, avoid increasing the thickness of the battery, and further improve the cycle performance of the battery.
[0062] In some embodiments of the present invention, in the silicon composite material, the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal is (50-100):(5-20):1. For example, in the silicon composite material, the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal can be 50:5:1, 50:10:1, 50:15:1, 50:20:1, 60:5:1, 60:10:1, 60:15:1, 60:20:1, 70:5:1, 70:10:1, 70:15:1, 70:20:1, 80:5:1, 80:10:1, 80:15:1, 80:20:1, 90:5:1, 90:10:1, 90:15:1, 90:20:1, 100:5:1, 100:10:1, 100:15:1 or 100:20:1, etc. Preferably, in the silicon composite material, the mass ratio of the silicon core, the metal organic hybrid glass and the liquid metal is (70-90): (8-12): 1. When the mass ratio of the silicon core, the metal organic hybrid glass and the liquid metal in the silicon composite material satisfies the above range, the silicon core, the metal organic hybrid glass and the liquid metal can be more fully matched, and the effects of the silicon core, the metal organic hybrid glass and the liquid metal can be fully utilized to obtain a silicon composite material with excellent energy density and self-healing ability, thereby improving the energy density and cycle performance of the battery.
[0063] In some embodiments of the present invention, the metal-organic hybrid glass comprises metal ions and ligands, the metal ions comprising at least one of copper ions, zinc ions, cobalt ions, iron ions, ferrous ions, zirconium ions, aluminum ions and chromium ions, and the ligands comprising at least one of 1,3,5-benzenetricarboxylic acid, 2'-amino-[1,1':4',1"-terphenyl]-4,4"-dicarboxylic acid, terephthalic acid, dimethylimidazole, 2,5-dimethylterephthalic acid, 2,5-diaminoterephthalic acid and 2-amino-4,4'-biphenyldicarboxylic acid.
[0064] In some embodiments of the present invention, the micron-sized silicon material is at least one of micron-sized silicon carbide, micron-sized elemental silicon, micron-sized silicon oxide, micron-sized silicon nitrogen compound and micron-sized silicon alloy.
[0065] The second aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, the negative electrode active layer comprising a negative electrode active material, and the negative electrode active material comprises the silicon composite material of the first aspect.
[0066] In the present invention, the negative electrode active layer can be located on one surface of the negative electrode current collector or on both surfaces of the negative electrode current collector. The negative electrode active material in the negative electrode active layer of the present invention includes the silicon composite material of the first aspect, and the negative electrode active layer also includes a binder and a conductive agent.
[0067] The negative electrode sheet of the present invention comprises the silicon composite material of the first aspect, so the negative electrode sheet has excellent capacity and cycle performance, and when applied to a battery, can improve the energy density and cycle performance of the battery.
[0068] In some embodiments of the present invention, in the negative electrode active layer, the mass percentage of the silicon composite material is 2-50%, for example, the mass percentage of the silicon composite material can be 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc. When the mass percentage of the silicon composite material in the negative electrode active layer meets the above range, the role of the silicon composite material can be fully exerted to improve the energy density and cycle performance of the battery.
[0069] In some embodiments of the present invention, the sum of the mass percentages of gallium and indium in the negative electrode active layer is 0.01-0.04%. For example, the sum of the mass percentages of gallium and indium in the negative electrode active layer can be 0.01%, 0.02%, 0.03% or 0.04%. Preferably, in the negative electrode active layer, the mass percentages of silicon, gallium and indium can be (1-1.8): (0.0136-0.0148): (0.0052-0.0064). When the sum of the mass percentages of gallium and indium in the negative electrode active layer satisfies the above range, the negative electrode sheet including the negative electrode active layer can not only improve the energy density of the battery when applied to the battery, but also form a stable SEI film. The negative electrode sheet has excellent self-repairing ability and can improve the cycle performance of the battery.
[0070] In some embodiments of the present invention, in the color spectrum of the negative electrode sheet, the ratio of the peak height to the bottom width of the peak is greater than 40:1, for example, the ratio of the peak height to the bottom width of the peak is 50:1, 60:1, 70:1, 80:1 or 90:1, etc. In the color spectrum of the negative electrode sheet, the ratio of the peak height to the bottom width of the peak is greater than 40:1, indicating that the silicon composite material (i.e., active material) in the negative electrode sheet of the present invention is very densely stacked. The densely stacked silicon composite material can improve the powdering of the negative electrode sheet active layer caused by silicon expansion on the one hand, and on the other hand, it can improve the uniformity of the SEI film on the surface of the negative electrode sheet, improve the stability and dynamic performance of the negative electrode sheet, and thus improve the cycle capacity retention rate, furnace temperature performance and rate performance of the battery.
[0071] In the present invention, the color spectrum of the negative electrode sheet can be analyzed by comparing the spectral distribution of the SEM image of the negative electrode sheet of the present invention and the SEM images of other negative electrode sheets in different channels (for example, red, green and blue) to analyze the characteristics and differences of the negative electrode sheet of the present invention and other negative electrode sheets. The spectral distribution describes the frequency of occurrence of each intensity value in the image and is an important indicator of the statistical characteristics of the image. Specifically including: 1. Image acquisition and preprocessing: The SEM image of the negative electrode sheet of the present invention and the SEM image of other negative electrode sheets are imported for processing. Each SEM image can be regarded as a three-dimensional matrix composed of multiple channels, and each channel represents a specific wavelength (for example, RGB channel); 2. Spectral distribution calculation: The spectral distribution is calculated for each channel of each SEM image. The spectral distribution represents the frequency of each pixel intensity value (from 0 to 255) in the image. The spectral distribution can be obtained by calculating the histogram of the image; 3. Spectral comparison analysis: The spectral distribution of the two SEM images on the same channel is compared. By drawing the spectral distribution in the same coordinate system, the difference between the two images in different intensity values can be intuitively observed. During the comparison process, by comparing the frequency of each intensity value, the similarities and differences of the images on a specific channel can be determined. Analyze the spectral comparison graph to explain the differences in the spectral distribution of the two images on different channels. Through this comparison, conclusions can be drawn about material composition, structural characteristics, etc. Among them, the horizontal axis (X-axis): represents the pixel intensity value (Intensity) of the image. For each color channel, these values range from 0 to 255, where 0 represents the darkest and 255 represents the brightest; the vertical axis (Y-axis): represents the frequency (Frequency) of the pixel intensity value, which is the number of times each pixel intensity value appears in the image.
[0072] A third aspect of the present invention provides a battery, comprising the negative electrode sheet of the second aspect.
[0073] It can be understood that the battery also includes a positive electrode sheet, a separator, an electrolyte and an outer package. In the present invention, the positive electrode sheet, the separator and the negative electrode sheet can be stacked to form an electrode assembly of a laminated structure, and then the electrode assembly can be placed in an outer package, and the electrolyte can be injected into the outer package, and the battery can be formed after sealing and forming; the positive electrode sheet, the separator and the negative electrode sheet can also be stacked, and then wound to form an electrode assembly of a wound structure, and then the electrode assembly can be placed in an outer package, and the electrolyte can be injected into the outer package, and the battery can be formed after sealing and forming.
[0074] Since the battery of the present invention includes the negative electrode sheet of the second aspect, the battery has excellent cycle performance and energy density.
[0075] In some embodiments of the present invention, the electrolyte includes lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate in the electrolyte is c, mol / L; in the negative electrode sheet, the mass percentage w of the silicon composite material satisfies w:c=(10-30):1, for example, w:c can be equal to 10:1, 15:1, 20:1, 25:1 or 30:1, etc. Preferably, w:c=(15-25):1. When w:c satisfies the above range, during the charge and discharge process of the battery, the negative electrode sheet including the silicon composite material is not only not easy to expand, but also has excellent electrolyte wettability, which helps to improve the cycle performance and rate performance of the battery.
[0076] The inventors also found in the study that when the ohmic impedance of the battery of the present invention is less than 34mΩ, the membrane impedance is less than 13mΩ, and the charge transfer impedance is less than 30mΩ, the battery has a more excellent rate performance. Among them, the ohmic impedance represents the basic resistance inside the battery, which affects the energy efficiency and heat generation of the battery, and is usually obtained through high-frequency impedance measurement; the membrane impedance mainly refers to the impedance of the SEI film on the surface of the negative electrode sheet, reflecting the difficulty of lithium ions passing through the SEI film, which is usually reflected in the medium frequency range; the charge transfer impedance refers to the transfer impedance of the charge at the negative electrode sheet / electrolyte interface, reflecting the kinetic characteristics of the electrochemical reaction, and is usually manifested as a semicircular arc in the impedance spectrum in the medium and low frequency region.
[0077] Furthermore, the ohmic impedance of the battery is less than 33 mΩ, the membrane impedance is less than 12.5 mΩ, and the charge transfer impedance is less than 20 mΩ.
[0078] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0079] Example 1
[0080] The battery of this embodiment is prepared by a method comprising the following steps:
[0081] 1) Preparation of silicon composite materials
[0082] a. Preparation of MGs
[0083] Copper nitrate (Cu(NO 3 ) 2 ), zinc nitrate (Zn(NO 3 ) 2 ), cobalt nitrate (Co(NO 3 ) 2 ), 1,3,5-benzenetricarboxylic acid (BTC) and 2'-amino-[1,1':4',1"-terphenyl]-4,4"-dicarboxylic acid (amino-TPDC) are added into a ball mill in a molar ratio of 5:2:4:4:2; then appropriate ball milling media (such as stainless steel balls, ceramic balls, etc.) are added for ball milling treatment, and then the ball milling product is taken out from the ball milling jar, and the ball milling product is washed with DMF to remove unreacted precursors and by-products; then the solid product is separated by filtration; the solid product is dried in a vacuum drying oven at 120° C. for 12 hours to obtain MGs;
[0084] The ball milling medium is a zirconia ball with a diameter of 2-8 mm. During the ball milling process, the ball-to-material ratio is 5:1, the rotation speed is 400 rpm, and the time is 10 hours.
[0085] b. Preparation of LM
[0086] In an argon environment, 71 wt% gallium and 29 wt% indium were melted to form a liquid alloy; 200 mg of the liquid alloy was added to 2 mL of deionized water and treated with a probe ultrasound to form a LM suspension with a concentration of 100 mg / mL.
[0087] c. Preparation of silicon composite materials
[0088] mSi particles and MGs powder were added to LM suspension (mass ratio of the three was 80:10:1) to obtain a silicon composite material LM-MGs-mSi powder including a silicon core, LM and MGs from the inside out.
[0089] 2) Preparation of negative electrode
[0090] LM-MGs-mSi, artificial graphite, conductive carbon black (SP) and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 2:6:1:1, deionized water was added, and a negative electrode active slurry was obtained under the action of a vacuum mixer;
[0091] The negative electrode active slurry was evenly coated on both surfaces of a 8 μm thick copper foil, then dried at room temperature, and subsequently transferred to a 60° C. oven for drying for 24 h, and then cold pressed and cut to obtain a negative electrode sheet including a negative electrode active layer.
[0092] 3) Preparation of positive electrode
[0093] The positive electrode active material is lithium cobalt oxide (LiCoO 2), polyvinylidene fluoride (PVDF), and conductive carbon black (super P) are mixed in a mass ratio of 7:1:2, N-methylpyrrolidone (NMP) is added, and stirred in a vacuum stirrer to form a positive electrode active slurry with uniform fluidity;
[0094] The positive electrode active slurry was evenly coated on both surfaces of a 10 μm thick aluminum foil, placed in an oven at 60° C. to dry for 24 hours, and then rolled and cut to obtain a positive electrode sheet including a positive electrode active layer.
[0095] 4) Preparation of electrolyte
[0096] In a glove box filled with argon (H 2 O<0.1ppm, O 2 <0.1ppm), EC and DMC were mixed evenly in a volume ratio of 1:1, and then fully dried lithium hexafluorophosphate (LiPF 6 ) to form an electrolyte with a concentration of 1 mol / L.
[0097] 5) Preparation of batteries
[0098] The positive electrode sheet of step 3), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging aluminum foil, and the electrolyte of step 4) is injected into the outer packaging aluminum foil, and a battery is obtained after vacuum packaging, standing, forming, shaping and sorting processes;
[0099] The specific parameters of the battery are shown in Table 1 and Table 2.
[0100] The preparation methods of Examples 2 to 35 are substantially the same as those of Example 1, except for the differences shown in Table 1.
[0101] Comparative Example 1
[0102] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0103] Use mSi to replace silicon composites.
[0104] Comparative Example 2
[0105] The preparation method of the battery of this comparative example is basically the same as that of Example 1, except that:
[0106] 1) Preparation of silicon composite materials
[0107] a. Preparation of MOFs
[0108] HKUST-1 and Zn-BTC powders were physically mixed (all materials were purchased commercially) to form MOFs. In the MOFs, the molar ratio of HKUST-1 to Zn-BTC was 5:2.
[0109] c. Preparation of silicon composite materials
[0110] MOFs were used to replace MGs to form silicon composite material LM-MOFs-mSi powder.
[0111] Performance Testing
[0112] The following performance tests were performed on the silicon composite materials and batteries in the examples and comparative examples, and the results are shown in Tables 1 and 2;
[0113] 1. SEM test
[0114] The surface SEM images of the negative electrode sheets in Example 1 and Comparative Example 1 were obtained respectively. Figure 1 This is a surface SEM image of the negative electrode sheet in Example 1 of the present invention; Figure 2 This is a surface SEM image of the negative electrode sheet in Comparative Example 1 of the present invention. Figure 1 and Figure 2 It can be seen that compared with comparative example 1, the surface morphology of the negative electrode sheet in embodiment 1 is more complete. When the negative electrode sheet is used in a battery, it is not easy to break during the charge and discharge process of the battery, which is beneficial to the cycle performance of the battery.
[0115] 2. Color spectrum features
[0116] 1) Image acquisition and preprocessing: The SEM images of the negative electrode sheet of Example 1 and the SEM images of the negative electrode sheet of Comparative Example 1 are imported for processing. Each SEM image can be regarded as a three-dimensional matrix composed of multiple channels, and each channel represents a specific wavelength (such as RGB channel); 2) Spectral distribution calculation: The spectral distribution is calculated for each channel of each SEM image. The spectral distribution represents the frequency of each pixel intensity value (from 0 to 255) in the image. By calculating the histogram of the image, the spectral distribution can be obtained; 3) Spectral comparison analysis: The spectral distribution of the two SEM images on the same channel is compared. By drawing the spectral distribution in the same coordinate system, the difference between the two images at different intensity values can be intuitively observed. During the comparison process, by comparing the frequency of each intensity value, the similarity and difference of the image on a specific channel can be determined. Analyze the spectral comparison diagram to explain the difference in spectral distribution of the two images in different channels. Through this comparison, conclusions about material composition, structural characteristics, etc. can be drawn. Among them, the horizontal axis (X-axis) represents the pixel intensity value (Intensity) of the image. For each color channel, these values range from 0 to 255, where 0 represents the darkest and 255 represents the brightest; the vertical axis (Y-axis) represents the frequency of occurrence of the pixel intensity value (Frequency), which is the number of times each pixel intensity value appears in the image.
[0117] Figure 3 This is a first spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1; Figure 4 The second spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1; Figure 5 This is a third spectrum distribution diagram of the negative electrode sheet in Example 1 of the present invention and the negative electrode sheet in Comparative Example 1. Figure 3-5 It can be seen that the peak of the spectrum curve in Example 1 is relatively high, which indicates that the negative electrode sheet in Example 1 has just the right integrity and is not easy to break when used in a battery, thus helping to improve the cycle performance of the battery.
[0118] 3. Specific surface area (BET) and pore size distribution of silicon composite materials
[0119] Sample pretreatment conditions: temperature: 150℃ to 200℃; time: 6 to 12 hours; vacuum degree: <10^ -5 Torr;
[0120] Nitrogen adsorption experimental conditions: Adsorption gas: nitrogen (N 2 ); Temperature: 77K (liquid nitrogen temperature); Pressure range: 0.01 to 1.0 relative pressure (P / P 0 ); Number of points of adsorption isotherm: 30 to 50 points, covering low pressure to high pressure region;
[0121] Data analysis method: BET: obtained by linear fitting from the relative pressure range of 0.05 to 0.3;
[0122] Pore size distribution calculation: The pore size distribution was extracted from the adsorption branch or the desorption branch using the BJH (Barrett-Joyner-Halenda) method.
[0123] Figure 6 is a pore size distribution diagram of the silicon composite material in Example 1 of the present invention. Figure 6 It can be seen that the pore size distribution of the silicon composite material of Example 1 is 1.3-2.7 nm.
[0124] 4. CO 2 Adsorption enthalpy
[0125] Multi-temperature adsorption experimental conditions: Adsorption gas: carbon dioxide (CO 2 ); Temperature range: 273K, 298K and 323K; Pressure range: 0 to 1 bar; Number of adsorption isotherm points: at least 15 points per temperature, covering low pressure to high pressure regions;
[0126] Pretreatment conditions: Temperature: the same pretreatment temperature as nitrogen adsorption; Time: 6 to 12 hours; Vacuum: <10^ -5 Torr;
[0127] Calculation method of adsorption enthalpy: Clausius-Clapeyron equation: The Clausius-Clapeyron equation is used to calculate the adsorption enthalpy through the pressure values at different temperatures with the same adsorption amount;
[0128] Fitting method: Linear fit the data to determine the enthalpy value.
[0129] 5. Indium content and gallium content
[0130] The negative electrode active layer in the negative electrode sheet of the embodiment and the comparative example was scraped off and washed with aqua regia (HCl and HNO 3 The mixture was dissolved and diluted and measured by ICP.
[0131] 6. EIS
[0132] Equipment: Electrochemical workstation
[0133] Method: Connect the positive and negative electrodes of the battery to the working electrode (WE) and the counter electrode (CE) respectively, and measure the frequency range: 0.01Hz to 1MHz. AC voltage amplitude: 5mV or 10mV.
[0134] Figure 7 1 is the EIS curve of the battery in Example 1 of the present invention and Comparative Example 1. Figure 7It can be seen that the membrane impedance and charge transfer impedance of the battery in the embodiment of the present invention are significantly smaller than those of the battery in comparative example 1, indicating that the composite silicon material of the present invention can form a SEI film with lower impedance at the negative electrode.
[0135] 7. Capacity retention rate and thickness expansion rate
[0136] Keep the temperature at 25℃ for 30min, charge at constant current XC (see Table 1 for X) to 4.53V, charge at constant voltage 4.53V, cut off at 0.3C, and discharge at 0.7C to 3V. Perform 200 charging cycles according to this charging system and calculate the capacity retention rate.
[0137] The initial fully charged thickness P0 and the fully charged thickness P after the cycle were measured, and the thickness expansion ratio was calculated as (P-P0) / P0×100%.
[0138] 8. First effect
[0139] 25℃ constant temperature for 30min, XC (X see Table 1 for details) constant current charge to 4.53V, 4.53V constant voltage charge, 0.3C cut-off; 0.7C discharge to 3V. Calculate the first efficiency = (first discharge capacity / first charge capacity) × 100%.
[0140] It should be noted that the test conditions of the multiple embodiments and comparative examples are substantially the same, the only difference being that the magnifications of Embodiment 2 and Embodiment 3 are different from those of the other embodiments.
[0141] Table 1
[0142]
[0143]
[0144] In Table 1, the pore size refers to the maximum value within the pore size distribution range; In+Ga refers to the sum of the mass percentages of gallium and indium in the negative electrode active layer.
[0145] Table 2
[0146]
[0147] It can be seen from Table 2 that the battery in the embodiment of the present invention has lower ohmic impedance, touch impedance and charge transfer impedance, and the battery has better first efficiency, capacity retention rate and lower thickness expansion rate, indicating that the silicon composite material of the present invention, when applied to a battery, can reduce the impedance of the battery, improve the first efficiency and cycle performance of the battery.
[0148] Furthermore, it can be seen from Examples 1 and 4 to 7 that by selecting the Dv50 of the silicon core of the silicon composite material, the impedance of the battery can be further reduced, the first efficiency and capacity retention rate of the battery can be improved, and the thickness expansion rate of the battery can be reduced.
[0149] It can be seen from Examples 1, 8 and 9 that by making the BET of the silicon composite material meet the range of 200-2000 m 2 / g, the obtained battery has lower impedance and thickness expansion rate, and has better first efficiency and capacity retention rate; It can be seen from Examples 1 and 9 that when the BET of the silicon composite material meets 800-2000m 2 / g, the battery's initial efficiency and capacity retention rate can be further improved, and the battery's impedance and thickness expansion rate can be reduced.
[0150] It can be seen from Example 1 and Example 10 that by selecting the pore size of the silicon composite material, the impedance of the battery can be further reduced, the first efficiency and capacity retention rate of the battery can be improved, and the thickness expansion rate of the battery can be reduced.
[0151] It can be seen from Examples 1 and 12 to 16 that by selecting the Dv50 of the silicon composite material, the impedance of the battery can be further reduced, the first efficiency and capacity retention rate of the battery can be improved, and the thickness expansion rate of the battery can be reduced. It can be seen from Examples 12 to 15 that when the Dv50 of the silicon composite material is 35-50μm, the obtained battery has better first efficiency and capacity retention rate, and has lower thickness expansion rate and impedance.
[0152] It can be seen from Example 1, Example 17 and Example 18 that when the aspect ratio of the silicon composite material is 1-5, the obtained battery has better first efficiency, capacity retention rate, and lower impedance and thickness expansion rate; it can be seen from Example 1 and Example 17 that when the aspect ratio of the silicon composite material is 1-2, the obtained battery has better first efficiency, capacity retention rate, and lower impedance and thickness expansion rate.
[0153] It can be seen from Example 1 and Example 20 to Example 23 that by selecting the indium content and the gallium content in the total mass of indium and gallium, the first efficiency and capacity retention rate of the battery can be improved, and the impedance and thickness expansion rate of the battery can be reduced.
[0154] It can be seen from Example 1 and Implementation 30 that by selecting the content of the silicon composite material in the negative electrode sheet, the ratio of the content of the silicon composite material in the negative electrode sheet of the battery to the concentration of lithium hexafluorophosphate in the electrolyte can be optimized, further improving the first efficiency and capacity retention rate of the battery, and reducing the impedance and thickness expansion rate of the battery; It can be seen from Example 1 and Implementation 24 to Example 29 that when the ratio of the mass percentage of the silicon composite material in the negative electrode sheet to the concentration of lithium hexafluorophosphate in the electrolyte is (10-30): 1, the obtained battery has a lower impedance and thickness expansion rate, and has a higher first efficiency and capacity retention rate. It can be seen from Example 1 Implementation 24 to Example 28 that when the ratio of the mass percentage of the silicon composite material in the negative electrode sheet to the concentration of lithium hexafluorophosphate in the electrolyte is (15-25): 1, the obtained battery has a lower impedance and thickness expansion rate, and has a higher first efficiency and capacity retention rate;
[0155] It can be seen from Example 1 and Example 31 to Example 33 that by selecting the sum of the mass percentages of indium and gallium in the negative electrode active layer, the first efficiency and capacity retention rate of the battery can be improved, and the impedance and thickness expansion rate of the battery can be reduced.
[0156] It can be seen from Example 1 and Example 34 that by selecting the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal in the silicon composite material, the sum of the mass percentages of indium and gallium in the silicon composite material can be optimized, thereby improving the first efficiency and capacity retention rate of the battery, and reducing the impedance and thickness expansion rate of the battery;
[0157] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The above are only preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of protection of the present invention.
Claims
1. A silicon composite material, characterized in that: The silicon composite material comprises liquid metal gallium and indium, wherein the sum of the mass percentages of gallium and indium is 0.05-0.2%.
2. The silicon composite material according to claim 1, characterized in that: Based on the total mass of the gallium and indium, the mass percentage of gallium is 68-74%, and the mass percentage of indium is 26-32%.
3. The silicon composite material according to claim 1, characterized in that: The silicon composite material comprises a silicon core, an intermediate layer and an outer layer; The middle layer is located on at least a portion of the surface of the silicon core, and the outer layer is located on at least a portion of the surface of the middle layer; The middle layer includes liquid metal gallium and indium, the outer layer includes metal-organic hybrid glass, and the silicon core is micron-sized silicon material.
4. The silicon composite material according to claim 3, characterized in that: The Dv50 of the silicon core is 5-30 μm; Preferably, the Dv50 of the silicon core is 20-30 μm.
5. The silicon composite material according to claim 3 or 4, characterized in that: The specific surface area of the silicon composite material is 200-2000m 2 / g; and / or, The pore size of the silicon composite material is 1.3-2.7 nm; and / or, The Dv50 of the silicon composite material is 10-50 μm; and / or, The aspect ratio of the silicon composite material is 1-5; and / or, The CO2 adsorption enthalpy of the silicon composite material is 10-40 kJ / mol.
6. The silicon composite material according to claim 5, characterized in that: The specific surface area of the silicon composite material is 800-2000m 2 / g; and / or, The Dv50 of the silicon composite material is 35-50 μm; and / or, The aspect ratio of the silicon composite material is 1-2; and / or, The CO2 adsorption enthalpy of the silicon composite material is 15-30 kJ / mol.
7. The silicon composite material according to claim 3, characterized in that: In the silicon composite material, the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal is (50-100): (5-20): 1; Preferably, in the silicon composite material, the mass ratio of the silicon core, the metal-organic hybrid glass and the liquid metal is (70-90):(8-12):
1.
8. The silicon composite material according to claim 3, characterized in that: The metal organic hybrid glass comprises metal ions and ligands, wherein the metal ions include at least one of copper ions, zinc ions, cobalt ions, iron ions, ferrous ions, zirconium ions, aluminum ions and chromium ions, and the ligands include at least one of 1,3,5-benzenetricarboxylic acid, 2'-amino-[1,1':4',1"-terphenyl]-4,4"-dicarboxylic acid, terephthalic acid, dimethylimidazole, 2,5-dimethylterephthalic acid, 2,5-diaminoterephthalic acid and 2-amino-4,4'-biphenyldicarboxylic acid; And / or, the micron-sized silicon material is at least one of micron-sized silicon carbide, micron-sized elemental silicon, micron-sized silicon oxide, micron-sized silicon nitrogen composite and micron-sized silicon alloy.
9. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material, and the negative electrode active material comprises the silicon composite material according to any one of claims 1 to 8.
10. The negative electrode sheet according to claim 9, characterized in that: In the negative electrode active layer, the mass percentage of the silicon composite material is 2-50%; And / or, the sum of the mass percentages of gallium and indium is 0.01-0.04%; preferably, in the negative electrode active layer, the mass percentages of silicon, gallium and indium are (1-1.8): (0.0136-0.0148): (0.0052-0.0064).
11. The negative electrode sheet according to claim 9 or 10, characterized in that: In the color spectrum of the negative electrode sheet, the ratio of the peak height to the peak bottom width is greater than 40:
1.
12. A battery, characterized in that: A negative electrode sheet comprising any one of claims 9 to 11.
13. The battery according to claim 12, characterized in that The negative electrode sheet also includes an electrolyte, wherein the electrolyte includes lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate in the electrolyte is c, mol / L; and the mass percentage w of the silicon composite material in the negative electrode sheet satisfies: w:c=(10-30):1; Preferably, w:c=(15-25):
1.
14. The battery according to claim 12, characterized in that The battery has an ohmic impedance of <34 mΩ, a membrane impedance of <13 mΩ, and a charge transfer impedance of <30 mΩ; Preferably, the battery has an ohmic impedance of <33 mΩ, a membrane impedance of <12.5 mΩ, and a charge transfer impedance of <20 mΩ.
Citation Information
Patent Citations
Silicon carbon composite material, fabrication method thereof, anode material and battery
CN105742599A
Negative electrode materials of silicon-liquid metal composite lithium battery and preparation method
CN106953075A
Application of gallium / indium doped zinc oxide in lithium ion battery anode material coating layer, and lithium ion battery anode material
CN109742358A
Lithium ion battery negative electrode material with multi-stage conductive structure, and preparation method thereof
CN113594440A
Positive electrode material, preparation method thereof and lithium ion battery
CN116741974A